2019
DOI: 10.48550/arxiv.1906.06514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PVRED: A Position-Velocity Recurrent Encoder-Decoder for Human Motion Prediction

Abstract: Human motion prediction, which aims to predict future human poses given past poses, has recently seen increased interest. Many recent approaches are based on Recurrent Neural Networks (RNN) which model human poses with exponential maps. These approaches neglect the pose velocity as well as temporal relation of different poses, and tend to converge to the mean pose or fail to generate naturallooking poses. We therefore propose a novel Position-Velocity Recurrent Encoder-Decoder (PVRED) for human motion predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…To learn the mapping between the complete feature set and hand joint accelerations, we used LSTM-based networks [28]. This choice was motivated by previous work, which showed that the ability of gated recurrent neural networks to learn long-term relationships between signals is instrumental in allowing the prediction of whole-body human motion [37,38]. Moreover, LSTM-based networks have recently been proved to be effective at predicting wrist position (3 DOFs) [39] and wrist flexion/extension (1 DOFs) [40] by tracking the EMG activity of 2-5 shoulder and arm muscles.…”
Section: E Network Architecturementioning
confidence: 99%
“…To learn the mapping between the complete feature set and hand joint accelerations, we used LSTM-based networks [28]. This choice was motivated by previous work, which showed that the ability of gated recurrent neural networks to learn long-term relationships between signals is instrumental in allowing the prediction of whole-body human motion [37,38]. Moreover, LSTM-based networks have recently been proved to be effective at predicting wrist position (3 DOFs) [39] and wrist flexion/extension (1 DOFs) [40] by tracking the EMG activity of 2-5 shoulder and arm muscles.…”
Section: E Network Architecturementioning
confidence: 99%
“…Nonlinear function approximators such as Gaussian Processes [24] or Deep Neural Networks [9], [25] have been used to regress large databases of human movement. Recurrent Neural Networks (RNN) are state of the art for predicting short-term high dimensional movements [8], [9], [26].…”
Section: B Human-motion Predictionmentioning
confidence: 99%
“…Thus, we need a predictive function h t+1:T = f (h 0:t , g * ) that computes a trajectory of future human states h t+1:T given previous observed states h 0:t and a goal g * . We use VRED, a recurrent neural network-based model for predicting motion [8] and make it goal-conditioned by adding a three-dimensional position g t to the input of the network at every timestep (see Figure 2). The goal input g t is relative to the coordinate frame of the human and thus changes every timestep.…”
Section: B Long-term Motion Prediction Using Hierarchiesmentioning
confidence: 99%
See 2 more Smart Citations